SUSTAINABLE TOURISM DEVELOPMENT OF MOUNTAIN TOURISM DESTINATIONS IN SERBIA - Kostić, Marija; Lakićević, Marija; Milićević, Snežana (Economics of Agriculture, 2018)
Tourism represents the fastest growing branch of economy, which is focused on the realization of economic effects. In the previous period of tourism development, no account was taken of natural resources and the environment. Contemporary trends indicate the existence of a growing demand for preserved natural resources аnd ecologically clean environment. This trend has caused sustainable tourism development, which will establish a positive relationship between the tourism development and the preservation of the environment. This paper presents the fundamentals of sustainable tourism development. Serbias mountain areas have a preserved potential of natural resources and the environment, which are the basis for the development of sustainable tourism. The aim of paper is to analyze the previous tourism development of mountain tourist destinations in Serbia, such as Kopaonik and Tara. The indicators of sustainable tourism are tested in this paper, and the results will show whether the previous tourism development in these areas was sustainable or unsustainable.